Cavitation reduction of a flapper-nozzle pilot valve using continuous microjets. (April 2019) - Yang, He; Wang, Wen; Lu, Keqing; Chen, Zhanfeng
Highlights: The microjets could greatly reduce the cavitation in the flapper-nozzle valve. The effect of housing diameter, inlet pressure and null clearance is explored. The effectiveness of cavitation reduction is still notable at high inlet pressure. The proposed method of microjets on cavitation suppression may also work for other hydraulic valves. Abstract: The flow cavitation in the flapper-nozzle stage is one of the main factors that produce the flapper vibration and thus deteriorate the performance of the flapper-nozzle servo valves. This work proposes a novel method, deploying two continuous microjets around the main jet of each nozzle, to suppress the cavitation. The cavitation reduction using continuous microjets is numerically examined in detail by comparing the vapor fraction with and without the microjets at different inlet pressure, housing diameter and the null clearance. The mass flow rate measurements and the flow visualization are conducted to validate the numerical simulation. It is found that the cavitation in the flapper-nozzle stage is significantly reduced under the effect of the continuous microjets. And the flow cavitation exhibits a great dependence on the inlet pressure, housing diameter and the null clearance. In the traditional flapper-nozzle structure, the cavitation is strongly enhanced at high inlet pressure, small housing diameter or large null clearance. Nevertheless, the cavitation in the flapper-nozzle structure with the microjets is still remarkably suppressed at the same condition. This indicates that the continuous microjets are highly effective in reducing the cavitation of the flapper-nozzle valve.